Evaluasi Dan Perbaikan Alur Dan Navigasi Situs Web Fakultas Kedokteran Gigi (FKG) Universitas Brawijaya Dengan Menggunakan Pendekatan Human Centered Design (HCD) - Nabila Sarah Pradila; Hanifah Muslimah Az-zahra; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Faculty of Dentistry Universitas Brawijaya (FKG UB) is a faculty at Brawijaya University which was established in 2008. FKG UB provides a website as a medium for delivering information, most of which have menus that have been set in Surat Keputusan tentang Website UKPA Universitas Brawijaya. The background of the problems found as the basis of this research is that users find it difficult to find certain information, and the placement of content that is difficult to find. Then based on needs, FKG UB's website will experience the addition of some content. Based on these problems and needs, the researcher conducted an evaluation using tree testing by measuring aspects of success rate, directness, first click, and destination to find out more about problems in website flow and navigation, and also researchers conducted card sorting testing to structure information structure from the website without changing the provisions of Surat Keputusan tentang Website UKPA Universitas Brawijaya. Researcher used the Human Centered Design (HCD) approach to produce a sitemap recommendation as an information structure of the website, and recommend improvements in the form of design. This study produces recommendations for improvement that are appropriate to the needs of users, and evaluation of the design of solutions has been carried out to prove that in some of the same scenarios, the evaluation results add value.